Capsule phase microextraction methodology: Applications and future perspective - Shaikh Manirul Haque; Abuzar Kabir; Torki Zughaibi; Noorfatimah Yahaya; Bharti Jain; Rajeev Jain; Masoom Raza Siddiqui (Journal of Chromatography Open)
Extraction plays a crucial role in the quantitative analysis of analytes across various matrices, particularly in biological and other complex samples, where accurate detection and determination would be challenging without effective extraction. Over time, new extraction techniques have been developed to meet evolving analytical needs. Nevertheless, sample preparation often still involves conventional steps such as analyte extraction, filtration, protein precipitation, centrifugation, elution with organic solvents, and solvent evaporation.Among the latest advancements in this field is the Capsule Phase Microextraction (CPME) methodology, a green and sustainable technique. A key advantage of CPME is the reusability of microextraction capsules, which enhances cost-efficiency and environmental friendliness. The technique employs inorganic–organic hybrid sorbents and integrates multiple functions, such as filtration and diffusion, within a single device, thereby simplifying the extraction workflow.This review highlights various aspects of the CPME methodology, including a schematic overview of the extraction process and the instrumentation used for post-extraction analysis. It also provides detailed information on the types of sorbents and eluting solvents utilized, along with the specific analytes effectively extracted using this technique.